Proceedings of the 13th International Congress on Mathematical Education: ICME-13 - Kaiser, Gabriele (Cham Springer Nature, 2017)
teaching mathematics; learning mathematics; mathematics education
English
Keywords: Mathematics & science; teaching mathematics; learning mathematics; mathematics education